2011
DOI: 10.1093/icvts/ivr049
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted closure of post-sternotomy mediastinitis as compared to open packing

Abstract: Post-sternotomy mediastinitis is a rare but serious complication of cardiac surgery leading to prolonged hospital stay and higher mortality. In the last decades several treatment modalities have been described, of which vacuum-assisted closure (VAC) shows the most promising results. The aim of this study is to describe clinical outcomes of VAC as compared to open packing and to predict risk factors for mortality. We performed a retrospective analysis of 113 patients with mediastinitis undergoing VAC (n = 89) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 15 publications
2
47
0
4
Order By: Relevance
“…This wound-healing technique is based on the application of continuous or intermittent negative pressure to a wound, which results in arteriolar dilatation and, subsequently, determines wound perfusion and granulation tissue proliferation [57,85,93] . In vitro and clinical studies designed to determine the effect of NPWT lent convincing evidence of efficacy and safety in term of decrease of edema, exudation, and microbial colonization as well as reduction of inflammatory cytokine release [57,85,[98][99][100] . In case of diagnosis of DSWI, an early application of NPWT was associated to a faster healing and an increased likelihood of survival [18,97,101,102] .…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…This wound-healing technique is based on the application of continuous or intermittent negative pressure to a wound, which results in arteriolar dilatation and, subsequently, determines wound perfusion and granulation tissue proliferation [57,85,93] . In vitro and clinical studies designed to determine the effect of NPWT lent convincing evidence of efficacy and safety in term of decrease of edema, exudation, and microbial colonization as well as reduction of inflammatory cytokine release [57,85,[98][99][100] . In case of diagnosis of DSWI, an early application of NPWT was associated to a faster healing and an increased likelihood of survival [18,97,101,102] .…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
“…In case of diagnosis of DSWI, an early application of NPWT was associated to a faster healing and an increased likelihood of survival [18,97,101,102] . Moreover, several studies demonstrated shorter treatment duration and length of hospital stay, as well as lower costs in patients treated with NPWT [96,98,100,103] . NPWT was also successfully applied in the case of MRSA mediastinitis and as a temporizing treatment prior to secondary closure in mediastinitis due to Candida [90,104,105] .…”
mentioning
confidence: 99%
“…The incidence rate of mediastinitis has been reported to be 0.3-5% [7][8][9][10]. Mediastinitis after sternotomy is a severe complication, even in paediatric patients, and its treatment remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The following surgical treatments for mediastinitis have been reported: closed irrigation [11], muscle flaps [9], primary closure with drainage [12] and VAC [7,13,14].…”
Section: S Takahara Et Al / Interactive Cardiovascular and Thoracicmentioning
confidence: 99%
“…Besides an improved local perfusionand oxygenation, the quantitative bacterial florais rapidly reduced and the formation of scar tissue is stimulated. Several studies showed the benefits of a VAC therapy in terms of shorter hospitalizations, earlier secondary wound closure and a lower mortality compared to conventional therapy [9,10]. We used VAC therapy to treat our patients with mediasitinitis.…”
Section: Discussionmentioning
confidence: 99%